ANALISIS KUALITAS SUMBER DAYA APARATUR PADA BADAN KEPEGAWAIAN DAN PENGAMBANGAN SUMBER DAYA MANUSIA DAERAH KABUPATEN MOROWALI - Adi Siswanto (Journal of Social Sustainability Management, 2021)
Issues to be discussed in this study is How the Resource Quality Apparatus In Education and Training Employment Agency Morowali District. The method used in this research is using qualitative research methods.. Data processing procedures in this study using primary data processing derived from interviews and secondary data processing through theoretical analysis sourced from books, reports, photos, data and observations. The results showed Apparatus Quality Resources still needs to be improved. Knowledge (knowledge) employees still need to be improved due to the lack of formal education possessed employees, there are employees who do not understand to vision and mission of the organization, and employees who do not understand about the duties and functions of each. Skills (skill) employees still need to be improved. Lack of training employees to follow good leadership training and technical training resulting in functional skills possessed by employees in work duties and functions still need to be improved, other than that there are employees who have structural positions but have not followed the leadership training. Ability (Ability) employees from the aspects of employee discipline still needs to be improved because it is still often in employee who is absent without explanation, other than that there are employees who leave the office during working hours so as not maximum personnel administration services. On aspects of employee loyalty has been very good, but aspects of cooperation between employees still need to be improved. Cooperation among leaders is needed, so do not inflict ambigu for employees. Permasalahan yang akan dibahas dalam penelitian ini adalah Bagaimanakah Kualitas Sumber Daya Aparatur Pada Badan Kepegawaian dan Pengambangan Sumber Daya Manusia Daerah Kabupaten Morowali. Metode yang digunakan dalam penelitian ini adalah menggunakan metode penelitian kualitatif. Prosedur pengolahan data dalam penelitian ini menggunakan pengolahan data primer yang bersumber dari wawancara dan pengolahan data sekunder melalui analisis teoritis yang bersumber dari buku, laporan, foto, data dan hasil observasi. Hasil penelitian menunjukkan Kualitas Sumber Daya Aparatur masih perlu untuk ditingkatkan. Pengetahuan (knowledge) pegawai masih perlu untuk ditingkatkan dikarenakan minimnya pendidikan formal yang dimiliki oleh pengawai, masih terdapat pegawai yang belum memahami dan menerapkan visi misi organisasi, dan pegawai yang belum memahami tentang tugas pokok dan fungsi masing-masing. Keterampilan (skill) pegawai masih perlu untuk ditingkatkan. Kurangnya pegawai yang mengikuti diklat baik diklat kepemimpinan maupun diklat teknis fungsional mengakibatkan keterampilan yang dimiliki oleh para pegawai dalam mengerjakan tugas pokok dan fungsinya masih perlu untuk ditingkatkan, selain itu masih terdapat pegawai yang telah menduduki jabatan struktural tapi belum mengikuti diklat kepemimpinan. Kemampuan (Ability) pegawai dilihat dari aspek kedisiplinan pegawai masih perlu untuk ditingkatkan hal tersebut dikarenakan masih seringnya terdapt pegawai yang tidak hadir tanpa keterangan, selain itu masih terdapat pegawai yang meninggalkan kantor pada saat jam kerja sehingga tidak maksimalnya pelayanan administrasi kepegawaian. Pada aspek loyalitas pegawai sudah sangat baik namun aspek kerja sama antara pegawai masih perlu untuk ditingkatkan. Kerjasama antara para pimpinan sangat diperlukan agar tidak menimbulkan kebingunagan bagi para bawahannya.